Optimization of proteinase K incubation protocol duration during DNA extraction from oral squamous cell carcinoma FFPE samples - Meizarini, Asti; Puteri, Astari; Yasan, Yanna Debby Restifanny; Hussaini, Haizal Mohd (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2023)
Background: Formalin-fixed paraffin-embedded (FFPE) specimen archives are a valuable source of sample material for molecular biological analysis. However, the DNA isolated from FFPE samples is usually low in concentration and fragmented. Thus, it is necessary to optimize the FFPE DNA extraction protocol to obtain the best results. Proteinase K incubation is undoubtedly crucial in DNA extraction procedures, but this step is often not well explained in the manufacturer's manual. Purpose: This study aimed to find the optimal duration for proteinase K incubation protocols to achieve the highest DNA yields. Methods: Fifteen paraffin blocks of Oral Squamous Cell Carcinoma (OSCC) specimens were obtained, and the cancerous areas were microdissected into smaller cuts for DNA extraction. The samples were randomly divided into three groups (n=5) and subjected to three different proteinase K incubation protocols: one-hour incubation at 56ºC as per the manufacturer's instructions (Group I), 24-hour incubation at 56ºC (Group II), and 48 hours at room temperature with an additional four hours at 56ºC (Group III). The extracted DNA was then quantified using a Nanodrop spectrophotometer. The recorded data were analyzed using ANOVA-LSD. Results: The highest DNA concentration was found in Group III (107.74 ± 41.92), which was significantly higher compared to Group II (59.46 ± 30.32) and Group I (6.46 ± 1.97) (p<0.05). Conclusion: In conclusion, modifying the duration of proteinase K incubation protocols can lead to different DNA yield results. In this study, the most optimized protocol for proteinase K incubation, resulting in the highest DNA yields, was 48 hours at room temperature with an additional four hours at 56ºC.